The additive predictive value of arterial stiffness for outcome to endothelial glycocalyx and SCORE in middle age individuals: 6 years follow-up. (3rd October 2022) - Ikonomidis, I; Thymis, J; Koliou, G A; Simitsis, P; Katsanos, S; Pavlidis, G; Kousathana, F; Kostelli, G; Katogiannis, K; Kountouri, A; Triantafyllidi, H; Parissis, J; et al.
Abstract: Background/Aim: Arterial stiffness is involved in the clinical course of atherogenesis. We have previously shown that PBR, a marker of glycocalyx integrity is predictor of cardiovascular events in patients without established cardiovascular disease. The purpose of this study was to investigate whether altered arterial properties of the vessels confers predictively and additively to estimation of cardiovascular risk. Methods: Pulse wave velocity carotid-femoral (PWVc-f), the gold standard method to assess arterial stiffness, was measured non-invasively by Complior device. Increased PWV(c-f), especially above 10 m/s, indicates increased arterial stiffness. We measured baseline PWV(c-f) in 600 apparently healthy subjects (47.61±13.84 years old, 50.1% males), without established cardiovascular disease. We prospectively monitored the occurrence of major cardiovascular events (MACE-death, myocardial infarction, stroke and heart failure hospitalization) during a 6-year follow-up period using electronic records and clinic visits. Results: Fifty-seven MACEs were documented during follow-up. In univariate analysis, subjects with increased PWV were found to exert greater risk for MACEs (hazard ratio (HR): 1.09, 95% CI: 1.02–1.17, p=0.01). In all subjects, PWV predicted higher risk for MACEs in a model including PBR, sex, age, hyperlipidemia, diabetes, hypertension, current smoking, family history of coronary artery disease and treatment with ACEi/ARBs or lipid lowering agents (HR: 1.12; 95% CI: 1.04–1.17, p=0.029, net reclassification improvement (NRI): 23%; C-statistic: from 0.644 to 0.697). However, only in participants older than 50 years old, PWV was an independent and additive predictor of outcome when added in a model including PBR, SCORE, those risk factors not included in SCORE (diabetes, family history of CAD) and medication (HR: 1.09; 95% CI: 1.02–1.13, NRI: 23.8%, C-statistic increase from 0.703 to 0.762, p<0.01). Conclusion: Arterial stiffness is an independent and additive predictor to endothelial glycocalyx and SCORE for adverse outcome at 6 years follow-up in individuals over 50 years old. Funding Acknowledgement: Type of funding sources: None.